Development of Science Module Based on the Meaning of Temperature and Heat Meaning Learning Model - Fauziyah Khoirin Nisyah; Dinar Maftukh Fajar; Binar Kurnia Prahani; Andi Suhardi (IKIP Mataram, 2022)
This research is motivated by the rampant degradationvalues, attitudes, and character of students, especially junior high school students; In addition, there is also the lack of science learning resources owned by students that contain character education. The reseach used research and development (Reseach and Development / R & D) with the ADDIE approach, namely: Analysis, Design, Development, Implementation, Evaluation. Data analysis was carried out by qualitative analysis and quantitative analysis. The data analysis carried out is numerical (quantitative) and descriptive (qualitative) data. Numerical data (quantitative) in the form of numbers obtained from validators and student response questionnaires. While descriptive data (qualitative) in the form of suggestions/comments given by the validator during the validation process and students during the small-scale and large-scale test processes both written and unwritten. The results obtained from research that has been carried out in MTs are as follows. First, the level of validity of the science module based on the meaning learning model of 5 expert validators, namely 2 material experts 86.58%, 2 education experts 83.77%, and 1 science teacher 78.04%, an average of 82.79% in the very category. valid/usable without revision. Second, the response of students to the science module based on the meaning learning model with the results of the small group trial getting an average of 76.8% with the attractive/agree category with the number of students 5, then in the large group trial it got an average of 77,84% with the attractive/agree category with the number of students 30. The results of this study show that this module shows an increase in positive response and can be used as a learning material independently by students.